The role of tropocollagen in connective tissue regeneration in athletes – a narrative review - Malinowska, Marcelina; Bartela, Martyna (Quality in Sport, 2026)
Background: Tropocollagen is a complex biopolymer that serves as the fundamental structural unit of collagen. It is instrumental in maintaining the uniformity and mechanical properties of connective tissues. In athletes, continuous mechanical stress and micro-injuries necessitate efficient regeneration processes. Consequently, tropocollagen plays a critical role in the healing of tendons, ligaments, and connective tissues associated with muscles. Objective: The objective of the present study was to conduct a comprehensive review of the literature concerning the role of tropocollagen in tissue regeneration among athletes, as well as to emphasize the benefits associated with collagen supplementation. Material and methods: A narrative literature review was conducted based on peer-reviewed publications from 2015 to 2024. The literature searches were performed using the PubMed and Google Scholar databases. The analysis included review articles, experimental studies, and clinical research pertaining to collagen metabolism, tissue regeneration, and supplementation among physically active individuals. Results: Current data indicate that tropocollagen plays a significant role in regenerative processes by contributing to the remodeling of the extracellular matrix and enhancing the mechanical properties of connective tissues. Additionally, collagen supplementation may facilitate regenerative processes in athletes.